THE CORRELATION BETWEEN SOCIAL MEDIA INTENSITY USE AND MOTHER'S ANXIETY LEVEL (A CROSS-SECTIONAL STUDY IN PRIMIPAROUS MOTHERS KELURAHAN ROWOSARI SEMARANG) - Alifatush Shabrina; Titis Hadiati; Hang Gunawan Asikin; Widodo Sarjana (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Anxiety disorder is one of the most common psychological disorder that often occurs in mothers after childbirth. One factor that is considered to have a correlation with the prevalence of anxiety level is the intensity of the social media use. In using social media, people tend to compare themselves and their lives with those of others and there is pressure to feel accepted by social media stereotypes. This study wants to focus on seeing whether there is a relationship between the intensity of social media use and maternal anxiety levels. Methods: This study was a cross-sectional study of 47 primiparous mothers in Kelurahan Rowosari Semarang. The data collection including: social media use intensity that was examined by SONTUS questionnaire, mothers’ anxiety level examined by Zung questionnaire and family socio-economical circumstances. Data was analized using Spearman’s rank correlation coefficient. Results: The majority of respondents were in the group with low intensity social media use (89.4%). The level of respondents' anxiety assessed using the Zung questionnaire grouped 51.1% of patients in the group with no anxiety and 48.9% of patients in the group with mild anxiety. There were no patients classified as moderate or high anxiety group. Based on the results of statistical analysis showed no significant correlation between social media intensity use and mother's anxiety level in primiparous mothers in Kelurahan Rowosari Semarang (p=0,214). Conclusion: There were no significant correlation between social media intensity use and mother's anxiety level in primiparous mothers in Kelurahan Rowosari Semarang.